The Effect of Maritime Security Regime (ISPS Code) on World Supply of Seafarers - Anastasakos, Agisilaos; Goulielmos, Alexandros M.; Gatzoli, Androniki (SPOUDAI Journal of Economics and Business, 2014)
The efforts of IMO on the security of ports and ships after 11/9 are presented. IMO’s resolution on fatigue of crews -cause of marine accidents- is also presented. The introduction of ISPS code -carried out under the pressure of USA- made by a non holistic approach, created a number of issues involving and affecting seafarers. IMO and ILO, and other industry’s organizations, but USA, tried subsequently to correct this repercussion. ISPS created four issues: the fair treatment of seafarers –especially serious in USA ports; shore leave; SUA and PSI conventions, which all changed seafarers’ working conditions, analyzed here. Important is also the ‘criminalization of seafarers’, which had the most serious impact on crews. Moreover, examined is the possible impact of MLC 2006 Convention -in force since 2013- on seafarers supply. The efforts of OECD countries and EU, to reverse the falling supply of well qualified marine officers in last 10 years or so, showing in 2010 a deficit of 13,000 officers, are shown. This problem is more acute when world fleet grows, as this was the situation between 2003 and early 2013. OECD, EU, but Greece, also worried for the possible transfer of “shipowning know-how” from them… JEL Classification: J22; J81; J88; J830; J880.